2019
DOI: 10.1080/09571736.2019.1597146
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of language and literacy interventions in children and adolescents with English as an additional language (EAL)

Abstract: Objective: A synthesis of evidence discussing the effectiveness of language and literacy interventions in children with English as an additional language. Our key research questions were: 1) What intervention studies have been published since 2014 addressing the language and literacy development of children with English as an additional language? 2) What is the impact of those interventions? We sought to update a 2015 systematic review evaluating language and literacy outcomes for EAL children (Murphy & Unthia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The regression analysis further confirmed the importance of phonological awareness and expressive vocabulary for word reading, supporting a body of existing research (e.g. Muter and Diethelm 2001;Oxley and de Cat 2019) but did not support the additional input of maternal education and the number of books available at home (van Bergen et al 2017). A possible explanation for this may be because the vast majority of children in the present sample were average or above readers; stronger relationships between the home environment and reading performance may be observed for poorer readers.…”
Section: Discussionsupporting
confidence: 60%
“…The regression analysis further confirmed the importance of phonological awareness and expressive vocabulary for word reading, supporting a body of existing research (e.g. Muter and Diethelm 2001;Oxley and de Cat 2019) but did not support the additional input of maternal education and the number of books available at home (van Bergen et al 2017). A possible explanation for this may be because the vast majority of children in the present sample were average or above readers; stronger relationships between the home environment and reading performance may be observed for poorer readers.…”
Section: Discussionsupporting
confidence: 60%
“…Vocabulary knowledge, or lack thereof, is a prominent issue in educational spheres 3 at present, which is welcomed. As previously mentioned, there is some evidence that vocabulary-based interventions can lead to improvements on literacy measures (Murphy & Unthiah, 2015;Oxley & De Cat, 2018). However, these studies will not have included multi-word units in their measures and interventions and we argue here that they should also be included as our research is clearly indicative of their importance.…”
Section: The Role Of Vocabulary Knowledge In Reading Comprehensionmentioning
confidence: 96%
“…This body of research in general indicates that many children with EAL require greater support in English vocabulary which would likely improve their reading comprehension. Indeed, a review of intervention studies aimed at improving EAL children's language and literacy has shown that vocabulary interventions can indeed improve children's reading comprehension skills (see Murphy & Unthiah, 2015;Oxley & De Cat, 2018). These interventions demonstrate then, that it is possible to support the development of vocabulary knowledge in children with EAL through appropriate pedagogy, which, in turn, can have a positive impact on reading comprehension.…”
Section: Reading Comprehension In Students With Ealmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews indicate a lack of oral language interventions for EAL learners in the UK (Murphy and Unthiah, 2015; Oxley and de Cat, 2019). Despite this, a small number of studies do offer promise for oral language and vocabulary intervention with very young EAL learners in England.…”
Section: Introductionmentioning
confidence: 99%